Detection of vegetation stress and nutrient deficiencies by leaf laser-induced fluorescence imaging - Heisel, F; Sowinska, M; Eckert, C; Miehe, J A (INTERNATIONAL SYMPOSIUM ON URBAN TREE HEALTH, 1999)
A high spatial resolution fluorescence imaging set-up developed in our laboratory has been used to study the effects of several stress factors on the fluorescence characteristics of various plants. Measurement campaigns, of agricultural interest, have made obvious for example: a strong and specific heterogeneity of the chlorophyll emission distribution at the surface of vine leaves (Vitis Vinefera `Riesling') suffering from different mineral stress for increasing nitrogen fertilisation of wheat (Triticum aestivum L., `Soissons'), a readily decrease of the blue/red and blue/far-red emissions ratios, which were found the most sensitive indicators of a nitrogen deficiency in the case of apple-trees (Malus x domestica Borkh.cv.'Jonagold 2361') an effect of nitrogen supply on the chlorophyll emission intensities, in an opposite way for 355 nm excitation for the rosette leaves than for the leaves from the youngest branches for oak (Quercus ilex) and beech (Fagus sylvatica), an important enhancement of the chlorophyll emission when the solar irradiance during growth is strongly reduced.
Keywords: irradiance; mineral or nitrogen deficiency; vine